The lens capsule significantly affects the viscoelastic properties of the lens as quantified by optical coherence elastography - Mekonnen, Taye; Zevallos-Delgado, Christian; Zhang, Hongqiu; Singh, Manmohan; Aglyamov, Salavat R.; Larin, Kirill V. (Frontiers in Bioengineering and Biotechnology, 2023)
The crystalline lens is a transparent, biconvex structure that has its curvature and refractive power modulated to focus light onto the retina. This intrinsic morphological adjustment of the lens to fulfill changing visual demands is achieved by the coordinated interaction between the lens and its suspension system, which includes the lens capsule. Thus, characterizing the influence of the lens capsule on the whole lens's biomechanical properties is important for understanding the physiological process of accommodation and early diagnosis and treatment of lenticular diseases. In this study, we assessed the viscoelastic properties of the lens using phase-sensitive optical coherence elastography (PhS-OCE) coupled with acoustic radiation force (ARF) excitation. The elastic wave propagation induced by ARF excitation, focused on the surface of the lens, was tracked with phase-sensitive optical coherence tomography. Experiments were conducted on eight freshly excised porcine lenses before and after the capsular bag was dissected away. Results showed that the group velocity of the surface elastic wave, V, in the lens with the capsule intact (V=2.55±0.23 m/s) was significantly higher (p < 0.001) than after the capsule was removed (V=1.19±0.25 m/s). Similarly, the viscoelastic assessment using a model that utilizes the dispersion of a surface wave showed that both Young’s modulus, E, and shear viscosity coefficient, η, of the encapsulated lens (E=8.14±1.10 kPa,η=0.89±0.093 Pa∙s) were significantly higher than that of the decapsulated lens (E=3.10±0.43 kPa,η=0.28±0.021 Pa∙s). These findings, together with the geometrical change upon removal of the capsule, indicate that the capsule plays a critical role in determining the viscoelastic properties of the crystalline